Proceedings of the 2014 Workshop on Distributed User Interfaces and Multimodal Interaction 2014
DOI: 10.1145/2677356.2677661
|View full text |Cite
|
Sign up to set email alerts
|

Context-sensitive and Collaborative application for Distributed User Interfaces on tabletops

Abstract: This paper focuses on collaborative work on interactive tabletops. To optimize the travel time of team members (remote workplace, telecommuting, and so on), collaborative work is now often remotely done. This brings many user interfaces issues between distributed platforms of each member. In the domain of context-sensitive user interfaces, which aims at an adaptation to the users, the platforms and the environment, context models have been proposed in the literature. We propose, in this paper, a context model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Education [37,179,365] and health [3,87,217,363] have also been popular application domains, where there has been an emphasis on collaborative and distributed work. Education applications have primarily focused on supporting classroom capture [344], classroom presentation [37,117], educational games [29,71,195], and simulations of classroom activities [163,232,262,345,365]. Kreitmayer et al [179] present one of the few in-the-wild studies, where they observed collaborative activities in the classroom to inform the design of a group finance management activity with a shared tablet and large display.…”
Section: Application Domainsmentioning
confidence: 99%
“…Education [37,179,365] and health [3,87,217,363] have also been popular application domains, where there has been an emphasis on collaborative and distributed work. Education applications have primarily focused on supporting classroom capture [344], classroom presentation [37,117], educational games [29,71,195], and simulations of classroom activities [163,232,262,345,365]. Kreitmayer et al [179] present one of the few in-the-wild studies, where they observed collaborative activities in the classroom to inform the design of a group finance management activity with a shared tablet and large display.…”
Section: Application Domainsmentioning
confidence: 99%
“…Moreover, device coniguration is rarely considered. These projects assume that no interaction is required to pair devices together and that devices are already inter-connected [5,29,34,56]. Fine control over documents or other forms of content to share between devices is also something that is often overlooked, although this is a very common task for teachers.…”
Section: Managing Devices In Classroomsmentioning
confidence: 99%
“…It should be noted that the amenability of tangible interfaces for collaborative work has made them promising tools for facilitating collaboration over long distances by augmenting teleconferencing (see for example Bouabid et al, 2014;Gonzalez-Franco et al, 2015), and for strengthening communications in co-Foro de Educación, v. 14, n. 20, enero-junio 2016, pp. 305-325. e-ISSN: 1698-7802 located meetings by means of smart boards and digital Post-It notes (see for example Haller et al, 2010).…”
Section: Tangibles and Collaborationmentioning
confidence: 99%